2005
DOI: 10.1158/1055-9965.epi-04-0501
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms ofMethionine SynthaseandMethionine Synthase Reductaseand Risk of Squamous Cell Carcinoma of the Head and Neck: a Case-Control Analysis

Abstract: Although tobacco and alcohol use are the major risk factors, folate deficiency has been implicated in the risk of squamous cell carcinoma of the head and neck (SCCHN). We hypothesized that polymorphisms of methionine synthase (MTR) and methionine synthase reductase (MTRR) in the folate metabolic pathway are associated with SCCHN risk. In a hospital-based case-control study of 721 SCCHN cases and 1,234 controls of non-Hispanic Whites, frequency matched by age, sex, and smoking status, we genotyped the MTR A2756… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 28 publications
0
40
2
2
Order By: Relevance
“…The results also show that men with head and neck cancer had a higher frequency of the G polymorphic allele than men with no history of cancer, thus supporting the results of Kruszyna et al (24), who showed that the frequency of the G allele was 1.55 times higher in male patients with laryngeal cancer compared to male controls. Our findings did not confirm those of Zhang and et al (22), who reported that the MTR 2756AG genotype is associated with an increased risk for this type of cancer, especially in younger individuals, women and former smokers.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The results also show that men with head and neck cancer had a higher frequency of the G polymorphic allele than men with no history of cancer, thus supporting the results of Kruszyna et al (24), who showed that the frequency of the G allele was 1.55 times higher in male patients with laryngeal cancer compared to male controls. Our findings did not confirm those of Zhang and et al (22), who reported that the MTR 2756AG genotype is associated with an increased risk for this type of cancer, especially in younger individuals, women and former smokers.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study did not detect any associations of the MTR A2756G polymorphism with the site of occurrence, aggressiveness, tumor extension, or lymph node involvement. Zhang et al (22) showed an increased frequency of the polymorphism related to tumors of the oral cavity, while Kruzsyna et al (24) did not find any association of this polymorphism with laryngeal cancer. After an exhaustive literature review, no previous studies were found regarding the possible association between this polymorphism and clinical histopathological parameters or with the risk of cancer development.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations